2015
DOI: 10.1016/j.crme.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Local boundary reflections in lattice Boltzmann schemes: Spurious boundary layers and their impact on the velocity, diffusion and dispersion

Abstract: This work demonstrates that in advection-diffusion Lattice Boltzmann schemes, the local mass-conserving boundary rules, such as bounce-back and local specular reflection, may modify the transport coefficients predicted by the Chapman-Enskog expansion when they enforce to zero not only the normal, but also the tangential boundary flux. In order to accommodate it to the bulk solution, the system develops a Knudsen-layer correction to the non-equilibrium part of the population solution. Two principal secondary ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, any non-zero diagonal weights, as the hydrodynamic weights, create the artificial Knudsen-type boundary layers [46], as the system response on the boundary restriction of the tangential advection-diffusion flux by the bounce-back rule [45]. Furthermore, the transverse velocity gradients in those induced boundarylayers produce the longitudinal numerical dispersion, in agreement with the Taylor mechanism and the three types of dispersions, namely, physical, truncation and boundary, are superposed.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…However, any non-zero diagonal weights, as the hydrodynamic weights, create the artificial Knudsen-type boundary layers [46], as the system response on the boundary restriction of the tangential advection-diffusion flux by the bounce-back rule [45]. Furthermore, the transverse velocity gradients in those induced boundarylayers produce the longitudinal numerical dispersion, in agreement with the Taylor mechanism and the three types of dispersions, namely, physical, truncation and boundary, are superposed.…”
mentioning
confidence: 73%
“…Further boundary analysis [45] has shown that the bounce-back drawback originates in its restriction of the tangential boundary flux, handled in hydrodynamic velocity sets by their diagonal links. In the accompanying work [46], we exactly quantify the difference in mean advection velocity and diffusion/dispersion for the specular reflection and bounce-back, in plug and parabolic flows. It has been also noted [45] that the specular reflection delivered identical solutions with the periodic condition on the straight solid wall in plug flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,29,52,54,97 However, it was recognized 14,107 that although the mirror reflection is suitable, the BB and "local" specular reflection (which returns the mass to departure node), enforce to zero not only the normal but also the tangential mass-flux components through the wall-inclined discrete-velocities. 26,33 The implicit interface tracking shares a similar tangential deficiency, because its advective-diffusive flux and scalarfield continuity conditions intrinsically couple 29 the BB and the (anti-BB) ABB Dirichlet rule. 26,56 The distribution moments can be regarded as the best indicators of the nonphysical solution behavior.…”
mentioning
confidence: 99%